A calibrated model of intraday settlement - Hector Perez-Saiz; Siddharth Untawala; Gabriel Xerri (Bank of Canada, 2018)
This paper estimates potential exposures, netting benefits and settlement gains by merging retail and wholesale payments into batches and conducting multiple intraday settlements in this hypothetical model of a single "calibrated payments system." The results demonstrate that credit risk exposures faced by participants in the system are largely dependent on their relative activity in the retail and wholesale payments systems. Participants experience lower exposures in the calibrated system owing to increased netting and significant gains through higher payment values and volumes. This result is reinforced when analyzing participant exposures in periods of stress, particularly during the Great Recession. Relative activity is also indicative of the variations in exposures across participants when implementing multiple batch sizes, especially because increasing batch sizes enhances the value and volume of payments accumulated, thus leading to higher netting and lower exposures. These results and further work may contribute to a better understanding of participant exposures and trade-offs arising from this potential system design.
Keywords: G21; G23; C58; 330; Econometric and statistical methods; financial stability; payment clearing and settlement systems